Lipid binding properties of a factor necessary for linoleic acid desaturation - Leikin, Alicia Isabel (1979)
Suspension and centrifugation of crude microsomes of rat liver in low ionic strength solution separated a soluble protein fraction that is necessary for the full activity of the linoleic acid desaturase. The fraction partially purified through Sephadex G-150 still retains lipids which are mainly constituted by phosphatidylcholine. Linoleic acid predominates in the fatty acid composition. By NaCl gradient centrifugation and electrophoresis in gelatinized cellulose acetate, the factor behaves like a lipoprotein. The factor binds linoleic acid and linolyl-CoA that are desaturated to γ-linolenic acid when incubated with washed microsomes. Albumin does not replace the factor.